Aryl hydrocarbon receptor deletion in cerebellar granule neuron precursors impairs neurogenesis. Issue 5 (17th August 2015) - Dever, Daniel P.; Adham, Zachariah O.; Thompson, Bryan; Genestine, Matthieu; Cherry, Jonathan; Olschowka, John A.; DiCicco‐Bloom, Emanuel; Opanashuk, Lisa A.
ABSTRACT: The aryl hydrocarbon receptor (AhR) is a ligand‐activated member of the basic‐helix‐loop‐helix/PER‐ARNT‐SIM(PAS) transcription factor superfamily that also mediates the toxicity of 2, 3, 7, 8‐tetrachlorodibenzo‐ p ‐dioxin (TCDD). Increasing evidence suggests that AhR influences the development of many tissues, including the central nervous system. Our previous studies suggest that sustained AhR activation by TCDD and/or AhR deletion disrupts cerebellar granule neuron precursor (GNP) development. In the current study, to determine whether endogenous AhR controls GNP development in a cell‐autonomous manner, we created a GNP‐specific AhR deletion mouse, AhR fx/fx /Math1 CRE/+ (AhR CKO). Selective AhR deletion in GNPs produced abnormalities in proliferation and differentiation. Specifically, fewer GNPs were engaged in S‐phase, as demonstrated by ∼25% reductions in thymidine ( in vitro ) and Bromodeoxyuridine ( in vivo ) incorporation. Furthermore, total granule neuron numbers in the internal granule layer at PND21 and PND60 were diminished in AhR conditional knockout (CKO) mice compared with controls. Conversely, differentiation was enhanced, including ∼40% increase in neurite outgrowth and 50% increase in GABARα6 receptor expression in deletion mutants. Our results suggest that AhR activity plays a role in regulating granule neuron number and differentiation, possibly by coordinating this GNP developmental transition. These studies provide novel insights for understanding the normal roles of AhR signaling during cerebellar granule cell neurogenesis and may have important implications for the effects of environmental factors in cerebellar dysgenesis. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 76: 533–550, 2016